ItzMe
Jun 24, 2020

#1**+2 **

We know how to compare quotients to 0. We start by subtracting 1 from both sides to get (3-z)/(z+1)-1 ≥0

We can simplify the left-hand side as (3-z)/(z+1)-1=(3-z)/(z+1)-(z+1)/(z+1)=(3-z-(z+1))/z+1=(2-2z)/(z+1)

so now our inequality is (2-2z0/(z+1) ≥ 0.

We can simplify this a bit by dividing both sides by 2 to get (1-z)/(z+1)≤0. Then, we multiply by -1 to turn the numerator on the left into . We must remember that multiplying by a negative means we reverse the inequality, so we have (z-1)/(z+1)≤0.

The quotient of two numbers is negative if and only if one of the numbers is negative and the other is positive, from which we find that (z-1)/(z+1) is negative for -1< z <1. We also could have built a table to analyze the possibilities:

z+1 | z-1 | (z-1)/(z+1) | |

z<-1 | - | - | + |

z=-1 | 0 | - | Undefined |

-1 | + | - | - |

z=1 | + | 0 | 0 |

z>1 | + | + | + |

The inequality is nonstrict, so we must also include any values of for which (z-1)/(z+1)=0. Therefore, the full solution is -1

ItzMeJun 25, 2020